Association between Serum Cotinine Levels and Bone Mineral Density: An Analysis of the National Health and Nutrition Examination Survey (NHANES) - Jian-Guo Fang; Duo-Jun Wang; Hao-Yu Yang; Hui Zhang; Jin-Yu Tong; Zai-Jun Lin (International Journal of Endocrinology)
Purpose. To investigate the relationship between serum cotinine and lumbar bone mineral density (BMD) among 7905 participants aged 30 years and over. Method. A total of 3945 men and 3960 women from the National Health and Nutrition Examination Survey 2011–2018 were included in this cross-sectional analysis. Independent variable was serum cotinine, which is a biomarker of cigarette exposure. The outcome variable was lumbar BMD. We investigated the associations of serum cotinine levels and lumbar BMD using multivariable linear regression models. Results. Serum cotinine concentration was negatively associated with lumbar BMD after adjustment of relevant covariables (β = −0.039, 95% CI: −0.078 to −0.014, P=0.005). However, in the subgroup analysis stratified by gender, this negative association remained only in women (β = −0.072, 95% CI: −0.132 to −0.012, P=0.019). Conclusion. Our study suggested that elevated serum cotinine level correlated with decreased lumbar BMD, especially in women. This finding indicated that reducing cigarette exposure and maintaining serum cotinine at a low level may be beneficial to bone health for adults.